Terorisme di Suriah dan Implementasi Arms Trade Treaty - Dina Yulianti; R. Widya Setiabudi Sumadinata (Indonesia Center for Middle East Studies, 2018)
The Syrian war that started in 2012 involves the global distribution of weapons to armed militias or non-state actors (NSAs) with enormous capital value. Meanwhile, the Arms Trade Treaty (ATT) entered into force on December 24, 2014. It restricts the weapons-producing countries to export weapons to NSAs known to commit genocide and direct attacks on civilians. In this article the authors will answer two main questions, firstly, how is the NSA profile in the Syrian conflict and who are the sources of their armory; and secondly, how is the impact of ATT implementation on weapons proliferation. The method used in this research is qualitative text analysis, i.e. reviewing the research documents that have been done before, the documents of ATT, and mass media coverages. The finding of this research is that ATT is not effective in preventing supply of weaponry into the hands of the NSA and it caused the continuing war of Syria.